Optimization of temperature conditions for the growth of large-size sapphire crystals by the method of horizontally directed crystallization - Grin, L.A.; Budnikov, A.T.; Sidelnikova, N.S.; Adonkin, G.T.; Baranov, V.V. (Functional Materials, 2013)
The coefficient of dislocation gliding over the planes of easy glide depending on the shape of the crystallization front, is determined. The regions of non-uniform distribution of thermal field in the crystal are established. Optimized are the temperature conditions for the growth of large-size (350×500×45 mm³) sapphire crystals by the method of horizontally directed crystallization. The change of the density of dislocations and of their distribution in the crystal bulk after correction of the technological growth conditions, is considered. It is shown that optimization of the axial, horizontal and vertical components of the temperature gradient makes it possible to improve uniformity of the thermal field distribution at the crystallization front in the process of the stationary crystal growth.